Answer:
The equation has no solution.
Step-by-step explanation:
Hi there!
First, let´s write the equation:
(√x + 3) + 6 = 3
To solve the equation, let´s subtract 6 to both sides of the equation:
√x + 3 = -3
subtract 3 to both sides of the equation:
√x = -6 (the square root of any number can´t be negative, but let´s solve it anyway and then check the solution).
Square both sides of the equation:
x = 36
Now, let´s check the solution:
(√x + 3) + 6 = 3
x = 36
(√36 + 3) + 6 = 3
(6 + 3) + 6 = 3
9 + 6 = 3
15 ≠ 3
Then, the equation has no solution.
Have a nice day!
7cos(x) + 1 = 6sec(x)
7cos(x) + 1 = 6/cos(x)
7cos^(x) + cos(x) = 6
7cos^(x) + cos(x) - 6 = 0
[7cos(x) - 6][cos(x) + 1] = 0
cos(x) = 6/7 , x = arccos(6/7) and
cos(x) = -1, x = 180
The answer is 46°.
The measure of an inscribed angle is equal to (1/2) the measure of the intercepted arc.
That means that, since ADC is 23 degrees, doubling that gives you 46 degrees, the measure of the intercepted arc.
Central angles are equal to the measure of the intercepted arc, which in this case is the same arc we just calculated.
Therefore it's 46.
Answer:
b
Step-by-step explanation:
The sum of angles in a triangle is 180°. Therefore,
x - 11 + 48 + 90 = 180
x + 127 = 180
x = 53°